بيان القراءات القرآنية وأثرها في الدراسات النحوية واللغوية دراسة وصفية تحليلية تطبيقية - Ahmed Ustman Fadhil (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2018)
This study aims at exposing the linguistic value of the Holy Qurans recitation and its effect on the Arabic linguistics and syntax. To achieve that, the research has been divided into three sections. The first section focused on the Holy Quran recitation among Basra and Kufa scholars; while the second section explained Holy Quran recitation in the light of the fundamental of Arabic syntax. The last section studied some holy Quran recitations that have influenced the Arabic syntax and linguistic studies which connected to the dialects. This study concludes with a conclusion which includes the most Important results of the study and recommendations.